A novel capture region of retro proportional navigation guidance law for intercepting high-speed nonmaneuvering targets. (May 2018) - Wang, Huaji; Lei, Humin; Ye, Jikun; Zhou, Jin; Zhai, Dailiang
In this paper, the capturability of retro proportional navigation against high-speed nonmaneuvering targets is analyzed. By using a modified polar coordinate, the equations describing the relative dynamics of the guidance problem become simple. The novel capture region of retro proportional navigation, which is the necessary and sufficient conditions for the interception, is derived by utilizing an auxiliary function. A new constraint condition is added to the derivation of the capture region, which can guarantee capture high-speed targets successfully. Meanwhile, the optimal aiming and the optimal position of interceptor are derived which are used to acquire the excellent initial conditions to capture the high-speed targets. The results show that the capture region of retro proportional navigation is larger compared with pure proportional navigation. Additionally, initial constraint conditions of interceptor in the case of planar engagement are described based on the capture region of retro proportional navigation, which can provide a reference for midcourse trajectory planning. Finally, simulation is performed to verify the feasibility of the initial conditions of the interceptor.